The polyamine spermine induces the unfolded protein response via the MAPK cascade in Arabidopsis - Sagor, G.H.M.; Chawla, Pratima; Kim, Dong Wook; Berberich, Thomas; Kojima, Seiji; Niitsu, Masaru; Kusano, Tomonobu (Frontiers in Plant Science, 2015)
In Arabidopsis three basic region leucine zipper (bZIP) transcription factor genes, bZIP17, bZIP28 and bZIP60, play crucial roles in the unfolded protein response (UPR). Previously we found that bZIP60 is one of the spermine-induces genes. Consequently we further investigated the response of all the three bZIP genes to spermine. Expression of bZIP17, bZIP28 and bZIP60, and also their target genes was activated by spermine application as well as in plants with elevated endogenous spermine levels. Furthermore, spermine activated the splicing of the bZIP60 transcript mediated by the ribonuclease activity of inositol-requiring enzyme 1 and also recruited bZIP17 and bZIP60 proteins from endoplasmic reticulum to nucleus. We therefore propose that spermine is a novel UPR inducer. Moreover, induction of UPR by spermine required calcium-influx to the cytoplasm and the genes for mitogen-activated protein kinase kinase 9 (MKK9), mitogen-activated protein kinase 3 (MPK3) and MPK6. The result indicates that spermine-induced UPR is mediated by the MKK9-MPK3/MPK6 cascade in Arabidopsis.